Cover Feature: Hybrids from the π−π Stacking of Graphene Oxide and Aromatic Sulfonic Compounds for Improved Proton Conductivity (ChemElectroChem 2/2018). Issue 2 (13th December 2017) - Shudo, Yuta; Karim, Mohammad Razaul; Ohtani, Ryo; Nakamura, Masaaki; Hayami, Shinya
Abstract : The Cover Feature shows the improvement in proton conductivity of graphene oxide (GO) owing to the intercalation of bulk sulfonic acid derivatives by means of π–π stacking. More information can be found in theCommunication by S. Hayami and co‐workers onpage 266 in Issue 2, 2018 .